2006
DOI: 10.1016/j.scitotenv.2006.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic emissions of isoprenoids and NO in China and comparison to anthropogenic emissions

Abstract: In this study, a regional dynamical model (WRF) is used to drive biogenic emission models to calculate high resolution (10 × 10 km) biogenic emissions of isoprene (C 5 H 8 ), monoterpenes (C 10 H 16 ), and nitric oxide (NO) in China. This high resolution biogenic inventory will be available for the community to study the effect of biogenic emissions on photochemical oxidants in China. The biogenic emissions are compared to anthropogenic emissions to gain insight on the potential impact of the biogenic emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 25 publications
7
42
1
2
Order By: Relevance
“…However, the link between isoprene emissions and increasing drought condition is more difficult to identify. Tingey et al (1981) and Pegoraro et al (2004b) found that for short-term soil moisture deficit lasting for a couple of days, the isoprene emission rate remains constant or even slightly increases in the initial stages of drought (Pegoraro et al, 2007). But as the soil moisture decreases below a certain level isoprene emission starts to decline as well.…”
Section: Soil Moisture Activity Factormentioning
confidence: 99%
See 4 more Smart Citations
“…However, the link between isoprene emissions and increasing drought condition is more difficult to identify. Tingey et al (1981) and Pegoraro et al (2004b) found that for short-term soil moisture deficit lasting for a couple of days, the isoprene emission rate remains constant or even slightly increases in the initial stages of drought (Pegoraro et al, 2007). But as the soil moisture decreases below a certain level isoprene emission starts to decline as well.…”
Section: Soil Moisture Activity Factormentioning
confidence: 99%
“…A reduction of isoprene emission rate by 64 % after 12 days of severe drought was observed for live-oak plants (Quercus virginiana Mill.) by Pegoraro et al (2004b) as well as a decrease by 50 % after 5 days (Tingey et al, 1981). The experimental findings of Pegoraro et al (2004a) served as a base for the parameterization of the impact of soil moisture stress on isoprene emissions in the MEGAN model.…”
Section: Soil Moisture Activity Factormentioning
confidence: 99%
See 3 more Smart Citations